Exploring Gamification Approaches for Enhancing Computational Thinking in Young Learners - Javier del Olmo-Muñoz; Andrea Bueno-Baquero; Ramón Cózar-Gutiérrez; José Antonio González-Calero (Education Sciences, 2023)
The integration of computational thinking (CT) in mathematics education is increasingly important due to its intersections with mathematical thinking and its role in the 21st century. Recent years have seen a growing interest in the use of innovative tools to enhance mathematics education, including the exploration of gamification techniques to improve student engagement. While previous research suggests that the inclusion of CT activities at an early age can positively impact students’ motivation and CT skills, the potential benefits of incorporating gamification techniques into CT instruction remain unexplored. In this study, we investigated the impact of shallow and deep gamification techniques on the CT skills and the intrinsic and extrinsic motivation of second-grade students in a blended teaching sequence that combined both unplugged and plugged CT activities. A quasi-experimental design was used with a control group and an experimental group. The findings suggest that both shallow and deep gamification techniques can be effective in improving CT skills in young students, but deep gamification may have a stronger impact on motivation. These results contribute to the growing body of literature on the integration of gamification techniques in CT instruction.